Molten salts and energy related materials. (8th June 2016) - Fray, Derek
Abstract : Molten salts have been known for centuries and have been used for the extraction of aluminium for over one hundred years and as high temperature fluxes in metal processing. This and other molten salt routes have gradually become more energy efficient and less polluting, but there have been few major breakthroughs. This paper will explore some recent innovations that could lead to substantial reductions in the energy consumed in metal production and in carbon dioxide production. Another way that molten salts can contribute to an energy efficient world is by creating better high temperature fuel cells and novel high temperature batteries, or by acting as the medium that can create novel materials that can find applications in high energy batteries and other energy saving devices, such as capacitors. Carbonate melts can be used to absorb carbon dioxide, which can be converted into C, CO and carbon nanoparticles. Molten salts can also be used to create black silicon that can absorb more sunlight over a wider range of wavelengths. Overall, there are many opportunities to explore for molten salts to play in an efficient, low carbon world.